A Comparative Study on Stress, Anxiety and Depression Between Nursing-Home Elderly Residents and Home-dwelling Elderly People - Roya Marsa; Seyed Jalal Younesi; Somaye Barekati; Maryam Ramshini; Hamed Ghyasi (University of Social Welfare & Rehabilitation Sciences, 2020)
Objectives: The increase in the aging population along with a variety of diseases and problems threatening their health and, on the other hand, socio-economic developments and changes in individual and family lifestyles, has increased the number of nursing homes. Considering the importance of the impact of living environment on various aspects of mental health, this study aimed to compare stress, anxiety and depression of the elderly living in nursing homes and those living at home. Methods & Materials: This is a descriptive comparative study with a cross-sectional design conducted in 2017. Using a convenience sampling method, 436 elderly people in Tehran including 218 home dwellers and 218 nursing-home residents were selected. Participants were evaluated through interview by the short-form version of Depression Anxiety Stress Scale (DASS-21). Comparisons between the two groups were made using independent t-test in SPSS v.20 software. Results: Mean and standard deviation of the DASS-21 score in elderly residents of nursing homes (37.75±11.34) was higher than in home dwellers (26.68±5.64). There were statistically significant differences in stress, anxiety and depression between the two groups (P≤0.05). Conclusion: Stress, anxiety and depression in the elderly living in nursing homes are more than in those living at home. Family participation in providing welfare and mental health care, supporting with appropriate insurance coverage, establishing day care centers, and supporting family caregivers can be very helpful to enhance their mental health.